Journal of Comparative Physiology B Biochemical, Systems, and Environmental Physiology - Heldmaier, Gerhard; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The journal publishes peer-reviewed original articles and reviews on the comparative physiology of invertebrate and vertebrate animals. Special emphasis in original articles is placed on integrative studies that elucidate mechanisms at the whole-animal, organ, tissue, cellular and/or molecular levels. Original articles should be full papers, as JCP-B does not publish short reports. Manuscripts that integrate findings at the molecular level into higher levels of organisation are particularly welcome. Review papers report on the current state of knowledge in an area of comparative physiology, and directions in which future research is needed. Aspects of particular interest include: Molecular and neuroendocrine control of metabolism Membrane transport and nutrient absorption Respiration and gas exchange Circulation and body fluids Energy and temperature relations Muscle and exercise physiology Energetics and endocrinology of reproduction Evolutionary aspects of physiology.
Keywords: Medicine; Human physiology; Biochemistry; Zoology; Animal Physiology; Biomedicine, general; Human Physiology; Zoology; Biochemistry, general